2015
DOI: 10.1637/11107-042115-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Disinfection Capacity of Slightly Acidic Hypochlorous Acid Water Towards Newcastle Disease Virus in the Air: AnIn VivoExperiment

Abstract: Existence of bioaerosol contaminants in farms and outbreaks of some infectious organisms with the ability of transmission by air increase the need for enhancement of biosecurity, especially for the application of aerosol disinfectants. Here we selected slightly acidic hypochlorous acid water (SAHW) as a candidate and evaluated its virucidal efficacy toward a virus in the air. Three-day-old conventional chicks were challenged with 25 doses of Newcastle disease live vaccine (B1 strain) by spray with nebulizer (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…SAHW is also an excellent anti microbial agent with a fast and strong capacity for inactivating pathogens. We previously confirmed its efficacy towards NDV in the air and AIV on surfaces, as well as its safety for chicks [ 13 , 14 ], and the present study documented its high performance for inactivation of bacteria in liquid and on porous and non-porous surfaces. Moreover, inactivation of bacteria in the dry condition was very easy, as even 50 ppm SAHW was able to inactivate them to an acceptable level.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…SAHW is also an excellent anti microbial agent with a fast and strong capacity for inactivating pathogens. We previously confirmed its efficacy towards NDV in the air and AIV on surfaces, as well as its safety for chicks [ 13 , 14 ], and the present study documented its high performance for inactivation of bacteria in liquid and on porous and non-porous surfaces. Moreover, inactivation of bacteria in the dry condition was very easy, as even 50 ppm SAHW was able to inactivate them to an acceptable level.…”
Section: Discussionsupporting
confidence: 80%
“…It has a high capacity for killing pathogens by irreversibly denaturing the critical components of cells, such as nucleic acids (DNA/RNA), mitochondria, enzymes and surface proteins [ 48 ]. Previously, we have reported that SAHW has a virucidal efficacy toward avian influenza virus (AIV) on surfaces [ 13 ] and Newcastle disease virus (NDV) in the air, along with confirmed safety for chicks [ 14 ]. In the present study, we evaluated sprayed SAHW for its efficacy in inactivating Salmonella Infantis and E .…”
mentioning
confidence: 99%
“…Chlorine has been shown to kill micro-organisms within very short period (within 5 sec) [10] and this short period allowed chlorine to inactivate Newcastle disease virus (NDV) in the air [12]. However, in the presence of organic matter, the efficacies were diminished [1, 10, 12].…”
mentioning
confidence: 99%
“…At RT and at 42°C, 200 ppm NaOCl inactivated L. pneumophilla to the undetectable level within 5 min in the absence of organic materials, whereas in the presence of organic materials it could not inactivate this bacterium to the undetectable level within 5 min (Tables 1and 2). Hakim et al [20] demonstrated that chlorine solution could inactivate micro-organisms within a very short time, and it was also shown that chlorine can inactivate Newcastle disease virus (NDV) in the air within a short period of time [17]. But, in the presence of organic materials, the inactivation efficacies of the chlorine solution were diminished [4, 17, 49].…”
Section: Discussionmentioning
confidence: 99%